Hygienic characteristics of changes in the nutritional status of adult population in the Omsk region during the implementation of Demography national project - O. V. Kozubenko; Yu. V. Menshchikova; M. S. Turchaninova; M. P. Menshchikov; E. А. Vilms (Фундаментальная и клиническая медицина, 2024)
Aim. To evaluate changes in nutritional status parameters among the adult population of the Omsk region during.Materials and Methods. The comparison of nutritional status parameters was conducted as a part of an experimental epidemiological study using a "before-after" design. The intervention consisted of activities carried out in the region from 2019 to 2023 under the federal project "Strengthening Public Health." In 2018, a representative sample (n = 241) was formed, stratified by age, gender, and residential area; in 2023, a similar sample (n = 506) was used. Nutritional status was assessed using somatometric, clinical, and laboratory methods.Results. We have documented a significant reduction in the prevalence of severe obesity (grades II-III, from 7.1 ± 1.1% to 2.4 ± 0.9%), and a trend towards a decrease in prevalence of underweight (from 5.4 ± 1.4% to 3.0 ± 0.8%; p = 0.078). In 2023, the proportion of individuals with overweight was 36.0 ± 2.1%, and 16.4 ± 2.4% of the adult population suffered from obesity. The prevalence of micronutrient deficiencies decreased significantly (p < 0.001). In 2023, deficiencies in vitamin D (61.8 ± 1.7%), folates (50.0 ± 3.2%), vitamins B1 (26.6 ± 2.8%), B6 (36.7 ± 3.1%), and E (28.5 ± 2.9%), magnesium (32.0 ± 2.0%), zinc (27.2 ± 2.8%), copper (36.0 ± 3.1%), iron (25.0 ± 1.7%), and selenium (31.2 ± 3.9%) were the most common. Compared to 2018, the prevalence of deficiencies in vitamins D, E, B1, B6, and folates significantly decreased (p < 0.05), while the provision of essential elements remained unchanged.Conclusion. The prevalence of various nutritional disorders among the adult population of the Omsk region reduced, as the implementation of the federal project «Strengthening Public Health» under the national project "Demography" improved the provision of vitamins.